Mejoramiento de la productividad de la línea de producción de snack de quinua de una empresa procesadora de cereales - Guerrón Ávila, Erik Javier (2018)
Lately, enterprises have seemed themselves, in the obligation on improving continuously in order to be more competitive. For this reason, managers should create conscience among the organization so there will be a willingness to changes. Indeed, continuous improvement gives the opportunity of having a competitive advantage to enterprises so, they should not reject this opportunity. The aim of this work is to improve the productivity of the fabrication line of quinua snack that belong to a cereal company, applying process management and times study. The cereal company, in which is based this project, has its headquarters in Quito, and its business is about quinua snack production, presenting to the market, a diversity of options such as: innovative products, great taste and healthy alternatives. The star product is the snack of 200 grams that represent the highest incomes for the company and this is why the studies of this work were developed in relation to this product. With the purpose of the objectives set out in this project are fulfilled, several activities were carried out, such as: process surveying, diagramming, identifying the value chain and the realization of a process map. Additionally, it was done: time study, standard time calculation, line balancing, man-machine diagrams and spaghetti diagrams. Finally, a simulation of both, the current and future situation was run in order to verify the differences with the proposed improvements. By using all the aforementioned tools and methodologies, if the improvement proposals are applied, the production of the company would increase by 4 times the current one. In addition, there would be additional monthly benefits of 8.278 dollars.